PENGARUH KARAKTER POSITIF SISWA TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PENGUKURAN LUAS MELALUI PENDEKATAN KONTEKSTUAL TEACHING AND LEARNING - Amriah; Babang Robandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to (1) enhancing student,s positive character in Area Meassurement skills (2)white enhance students' skills in measuring area through the contextual teaching and learning approach (CTL), and (3) examine whether the contextual approach to the concept of area can improve students' learning outcomes. The method used is qualitative with a descriptive and inductive analysis approach as explained by Rahmat. The results of the study show that at the initial stage, teachers did not fully understand the CTL approach with an average document analysis score of 2, observations of student learning activities averaged 1.75, and student learning outcomes reached an average of 69, which did not meet the Minimum Completeness Criteria (KKM). After a series of interventions through the application of the CTL approach, the results of teacher document analysis increased to 3.75, observations of student learning activities reached an average of 3.73, and student learning outcomes increased significantly with an average of 87. This increase indicates that the CTL approach is effective in improving teacher understanding, student learning activity, and student learning outcomes on the concept of area measurement. With the achievement of significant improvement, this study was stopped at this stage.